PEMBELAJARAN SENI TARI PADA ANAK USIA DINI DI SANGGAR SAORAJA ART’S KABUPATEN BONE - Rahman, Haryudi (EDUCHILD (Journal of Early Childhood Education), 2020)
Saoraja Art’s Studio is an art institution that trains more than 20 early childhood children. Art is a tool for expressing motion, sound picture and more. Motion is importen for children’s motor skills. The purpose of this study was to find out how to learn the art of dance at the Saoraja Art’s studio. By training the art of motoric dance dexterity, namely the movement to perform action in the form of dexterity and skill.Keyword: Dance, PAUD, learning,